L’expertise psychiatrique au service de la gouvernance ? - Olivier Dembinski (La Nouvelle Revue du Travail)
The article examines the process by means of which the New Public Management framework institutionalizes management expertise in the field of psychiatry. Conveyed by actors who have a stake in success, such expertise is the product of a hybridization between managerial and medical knowledge. Today it underpins the construction of an ideological state apparatus whose objective is to rationalize certain activities in psychiatry.